Porcine Epidemic Diarrhea Virus Nucleocapsid Protein Antagonizes Beta Interferon Production by Sequestering the Interaction between IRF3 and TBK1 - Ding, Zhen (American Society for Microbiology, 2014)
Porcine epidemic diarrhea virus (PEDV), a porcine enteropathogenic coronavirus, causes lethal watery diarrhea in piglets and results in large economic losses in many Asian and European countries. A large-scale outbreak of porcine epidemic diarrhea occurred in China in 2010, and the virus emerged in the United States in 2013 and spread rapidly, posing significant economic and public health concerns. Previous studies have shown that PEDV infection inhibits the synthesis of type I interferon (IFN), and viral papain-like protease 2 has been identified as an IFN antagonist. In this study, we found that the PEDV-encoded nucleocapsid (N) protein also inhibits Sendai virus-induced IFN-β production, IFN-stimulated gene expression, and activation of the transcription factors IFN regulatory factor 3 (IRF3) and NF-κB. We also found that N protein significantly impedes the activation of the IFN-β promoter stimulated by TBK1 or its upstream molecules (RIG-I, MDA5, IPS-1, and TRAF3) but does not counteract its activation by IRF3. A detailed analysis revealed that the PEDV N protein targets TBK1 by direct interaction and that this binding sequesters the association between TBK1 and IRF3, which in turn inhibits both IRF3 activation and type I IFN production. Together, our findings demonstrate a new mechanism evolved by PEDV to circumvent the host's antiviral immunity. IMPORTANCE PEDV has received increasing attention since the emergence of a PEDV variant in China and the United States. Here, we identify nucleocapsid (N) protein as a novel PEDV-encoded interferon (IFN) antagonist and demonstrate that N protein antagonizes IFN production by sequestering the interaction between IRF3 and TBK1, a critical step in type I IFN signaling. This adds another layer of complexity to the immune evasion strategies evolved by this economically important viral pathogen. An understanding of its immune evasion mechanism may direct us to novel therapeutic targets and more effective vaccines against PEDV infection.